The Contribution of Tuan Arshad Thalib Lubis in Fiqh al-Hadis: A Review of the Book Fatwa Beberapa Masalah - Mukhlis, Mukhlis; Yuslem, Nawir; Sulidar, Sulidar (Diroyah : Jurnal Studi Ilmu Hadis, 2024)
This article reviews the method of Fiqh al- ḥadīṣ applied by the tarjih mujtahid scholar, Tuan Arshad Thalib Lubis, by examining his book entitled “Fatwa on Some Issues.” The context of the study of hadith, which is full of debates, is the background for expanding the understanding of the application of this method in the context of Islamic law. The contentious context of had-ith studies serves as a background for expanding our understanding of the application of this method in the context of Islamic law. The research method used a literature study and inter-views with Tuan Arsyad's students with a qualitative-interpretative approach. The analysis was descriptive-critical, focusing on the method of interpreting hadith and assessing its credibility. The results show that Tuan Arshad's Fiqh al-ḥadīṣ method reflects the maturity of his thought and his analytical acumen, making a special contribution that enriches the understanding of the complexity or intricate details of the traditions, which includes an in-depth understanding of the context, sanad (chain of narrators), matan (text of the tradition), as well as its relationship with the rules of Fiqh al-ḥadīṣ through six main aspects. Tuan Arshad blends his perspective with the principles of the earlier muhaddithin, making him a guardian of the integrity of Islamic law. His contribution in bridging the scholarly legacy of muhaddithin with the dynamics of the times provides a strong foundation for relevant and accurate lawmaking. Focusing on the application of the Fiqh al-ḥadīṣ method, this paper affirms the full perspective of Tuan Arshad's contribution to hadith studies